Pelanggaran Maksim Kesantunan Berbahasa pada Novel “Teruslah Bodoh Jangan Pintar” Karya Tere Liye - Maghfiroh, Hayatin Nur; Tarmini, Wini (Universitas Muhammadiyah Surabaya, 2025)
This research aims to describe the forms of violations of language politeness maxims found in the novel